Genetic and environmental effects on age at first calving and calving interval of naturally bred Boran(zebu) cows in Ethiopia - Haile-Mariam, M.; Kassa-Mersha, H. (Cambridge University Press, 1994)
Factors affecting reproductive performance in Boran cattle were investigated. Twenty-four years of data from a Boran cattle breeding and improvement ranch in the Rift Valley of Ethiopia were analysed to examine genetic and environmental influence on age at first calving (AFC) and calving interval (CI) using an individual animal model. The mean AFC and CI were 41.8 months and 442 days, respectively. The h² values for AFC were 0.062 and 0.075 when estimated on the original and selected data, from which cows that did not calve after 5 years of age were deleted respectively. The values for CI were 0.037 and 0.043 when estimated on the original and selected data, from which cows with AFC higher than 5 years and CI longer than 2 years were deleted, respectively. The corresponding c² values (ration of permanent environmental variance to total) were 0.031 and 0.028 for the respective data sets. Parameter estimates of the original data from bivariate analysis were 0.012 (h²), 0.065 (h²), -0.054 and -0.176 for the first CI, AFC, their genetic and environmental correlation, respectively. The h² values estimated in a bivariate analysis of the first three CIs varied between 0.002 and 0.093. Year and season had significant effects on both traits. The annual genetic change for both traits was not significant while the solutions for year effects were highly variable. The regression of the solutions of year effects for AFC on year showed that it increased by about 10 days while the variation in CI was due to random year to year fluctuation.